Comparing Behavioral and Emotional Strengths of Students With and Without Emotional Disturbance. (December 2021) - Lambert, Matthew C.; January, Stacy-Ann A.; Gonzalez, Jorge E.; Epstein, Michael H.; Martin, Jodie
The present study investigated evidence of the construct validity of scores from the Behavioral and Emotional Rating Scale (BERS-3), which is a multi-informant assessment designed to measure the behavioral and emotional strengths of school-aged youth. The purpose of this research was to evaluate the degree to which BERS-3 scores differed between students with school-identified emotional disturbance and students without disabilities. Two nationally representative samples were used in this study: (a) 1, 575 students rated by teachers and (b) 793 youth who provided self-ratings. The results of multivariate multiple regression analyses supported the primary hypothesis that students with emotional disturbance would have lower scores on each of the five BERS-3 subscale scores compared to peers without disabilities. This finding held for both samples; however, differences between students with emotional disturbance and the peers without disabilities were substantially smaller for the youth self-ratings compared to teacher ratings. Implications for practice and directions for future research are also discussed.